Education, Skills and Social Justice in a Polarising World Between Technical Elites and Welfare Vocationalism (Taylor & Francis, 2022)
education, elites, justice, social skills, polarizing, welfare, world
English
Keywords: Education; education, elites, justice, social skills, polarizing, welfare, world